2009
DOI: 10.1002/ajhb.20976
|View full text |Cite
|
Sign up to set email alerts
|

Genetic composition of Brazilian population samples based on a set of twenty‐eight ancestry informative SNPs

Abstract: Ancestry informative SNPs can be useful to estimate individual and population biogeographical ancestry. Brazilian population is characterized by a genetic background of three parental populations (European, African, and Brazilian Native Amerindians) with a wide degree and diverse patterns of admixture. In this work we analyzed the information content of 28 ancestry-informative SNPs into multiplexed panels using three parental population sources (African, Amerindian, and European) to infer the genetic admixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
133
3
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(164 citation statements)
references
References 44 publications
19
133
3
9
Order By: Relevance
“…Although these data corroborate with previous studies in relation of major contribution of genomic ancestry 2,20 , it is possible to observe that there were differences between our data and these studies because we found a slightly larger percentage of African genomic ancestry and a slightly lower percentage of European genomic ancestry in the black and brown individuals. These differences could be mainly due to the socio-economic bias that exists in the Brazilian population.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Although these data corroborate with previous studies in relation of major contribution of genomic ancestry 2,20 , it is possible to observe that there were differences between our data and these studies because we found a slightly larger percentage of African genomic ancestry and a slightly lower percentage of European genomic ancestry in the black and brown individuals. These differences could be mainly due to the socio-economic bias that exists in the Brazilian population.…”
Section: Discussionsupporting
confidence: 44%
“…This emphasizes the fact that in a population where there is a high degree of admixture and where superfi cial physical traits can vary with age and environmental factors, only the self-declaration of ethnicity is not a good method for ethnic classifi cation 6,20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen ancestry informative markers with large differences in allelic frequency were previously selected to estimate genetic admixture (Moreno Lima et al 2007). Genotype data from three ethnic parental populations were used to adjust inference in admixed population: Sub-Saharan African (120 individuals), Amerindian (69 individuals) and European-American (78 individuals) (Smith et al 2004, Lins et al 2010a). The evaluation of population structure was performed using the Structure 2.1 software by means of Bayesian inference (Pritchard et al 2000).…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…Genotypes were determined using GeneScan Analysis Software, version 3.7 (Applied Biosystems) and Genotyper version 3.7 (Applied Biosystems). A detailed, optimized multiplex, singlebase extension protocol, with reagent concentrations and PCR thermocycling conditions, was described elsewhere (Lins et al , 2010a.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%